2019
DOI: 10.1093/hropen/hoy025
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial scratching prior to IVF; does it help and for whom? A systematic review and meta-analysis

Abstract: STUDY QUESTION What is the effect of endometrial scratching in patients with or without prior failed ART cycles on live birth (LBR) and clinical pregnancy rates (CPR)? SUMMARY ANSWER It remains unclear if endometrial scratching improves the chance of pregnancy and, if so, for whom. WHAT IS KNOWN ALREADY Endometrial scratching is hypothesized to improve embryo implantation in ART. Multiple studies have been published, but it remains unclear if… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
60
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 40 publications
3
60
0
2
Order By: Relevance
“… The statement above has also been proved by several recent meta‐analysis studies . However, in 2019, another two systematic reviews suggested that current evidence did not fully support performing EI with the purpose of improving success of a first ET attempt . Therefore, the clinical application of EI is still in controversial, especially for the frozen–thawed ET process due to the lack of evidence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… The statement above has also been proved by several recent meta‐analysis studies . However, in 2019, another two systematic reviews suggested that current evidence did not fully support performing EI with the purpose of improving success of a first ET attempt . Therefore, the clinical application of EI is still in controversial, especially for the frozen–thawed ET process due to the lack of evidence.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no consensus in the field up to date and the benefit of EI prior to embryo transfer is controversial. Specifically, some studies demonstrated that performing EI in luteal phase prior to in vitro fertilization (IVF)/ICSI improved implantation and clinical pregnancy rates, in the meanwhile, there are some studies denied such benefit of EI . It is important to point out that most previous studies focused on fresh embryo transfer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies had shown a potential benefit of the procedure in improving fertility performance in women with previous IVF failure undergoing a fresh cycle [13,14]. However, the most recent systematic review has reported no effect of the procedure on women undergoing IVF treatment with a previous one failed IVF cycle [23]. However, there is still uncertainty about the value of the procedure in women undergoing it for the first time [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…However, the most recent systematic review has reported no effect of the procedure on women undergoing IVF treatment with a previous one failed IVF cycle [23]. However, there is still uncertainty about the value of the procedure in women undergoing it for the first time [23][24][25].…”
Section: Discussionmentioning
confidence: 99%